PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI - Rizki Febrian; Sri Ekowati ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2023)
This study aims to determine the effect of leadership style and motivation on work productivity (a case study on employees of PT. Kimia Farma Bengkulu branch). This type of research is a quantitative descriptive research. The object of this research is the employees of PT. Kimia Farma Bengkulu. The sampling method is a saturated sampling technique. The number of respondents in this study were 40 respondents. The method of data collection is using the distribution of questionnaires. The data analysis technique used multiple linear regression analysis and hypothesis testing, namely t test and F test. The results of this study can be concluded that the variables of leadership style and motivation have a positive and significant effect on work productivity at PT. Pharmaceutical Chemistry. Partially, the two variables of leadership style and motivation have a positive and significant influence on work productivity. The better the leadership style and the better the motivation given in accordance with the employee's work, the work productivity will increase.  Keywords: Leadership Style, Motivation, Work Productivity